A case of Mycobacterium mucogenicum infection in a liver transplant recipient and a review of the literature. Issue 6 (17th October 2013) - Maybrook, R.J.; Campsen, J.; Wachs, M.E.; Levi, M.E.
Abstract Bacterial, viral, and fungal infections can be devastating in a postoperative liver transplant recipient on multidrug immunosuppressive therapy. Various atypical (nontuberculous mycobacteria [NTM]) mycobacterial infections have been reported in the solid organ transplant population, but to our knowledge, no cases of Mycobacterium mucogenicum infections have been reported. Here, we report a case of a patient with end‐stage liver disease secondary to primary biliary cirrhosis, model for end‐stage liver disease score of 29, who underwent deceased‐donor orthotopic liver transplantation, with her postoperative course complicated by multiple pleural effusions and peritonitis. Despite numerous courses of antibiotics, her condition did not improve. Acid‐fast bacilli cultures grew M. mucogenicum, which was then treated with appropriate antimicrobical therapy. M. mucogenicum, a rapidly growing NTM that can be present in water contamination, should be recognized as a potential source of infection, especially in the immunocompromised population.